2016
DOI: 10.21248/contrib.entomol.66.1.119-124
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the knowledge of the fauna of Ichneumonidae (Hymenoptera: Ichneumonoidea) from Iran.

Abstract: In dieser Arbeit werden 17 Arten der Unterfamilien Anomaloninae, Cremastinae, Cryptinae, Ctenopelmatinae, Ichneumoninae, Orthocentrinae, Pimplinae, Tersilochinae und Tryphoninae der Familie Ichneumonidae (Hymeno­ptera) aus verschiedenen Regionen Irans nachgewiesen. Drei Arten, Gelis anthracinus (Förster, 1850), Eusterinx (Dallatorrea) circaea Rossem, 1982 und Barycnemis agilis (Holmgren, 1860), sind Erstnachweise für die Fauna Irans.StichwörterHymenoptera, Ichneumonidae, faunistic list, new records, Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Hyposoter barretti (Bridgman, 1881)** (Fig. 1A) (Ghahari & Jussila, 2011) and Kerman provinces (Current study).…”
Section: Genus Hyposoter Förster 1869mentioning
confidence: 67%
“…Hyposoter barretti (Bridgman, 1881)** (Fig. 1A) (Ghahari & Jussila, 2011) and Kerman provinces (Current study).…”
Section: Genus Hyposoter Förster 1869mentioning
confidence: 67%
“…The majority of the taxonomic or biological studies on the genus Cotesia include the central and northern parts of Iran (Davatchi & Chodjai 1969;Modarres Awal 1997;Karimpour et al 2001 Samin et al 2015;Ghahari et al 2011b;Ghahari et al 2010 Ghahari et al 2009Ghahari et al , 2011aGhahari et al , 2011bGhahari et al , 2011cGhahari et al , 2011dGhahari et al , 2012aGhahari et al , 2012bLashkari Bod et al 2011;Naderian et al 2012;Ghahari & Fischer 2012;Sakenin et al 2012;Khajeh et al 2014;Samin 2015;Farahani et al 2016;Samin et al 2018). Prior studies reported 34 species of Cotesia from Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Lorestan (Ghahari et al, 2012a), Golestan (Sakenin et al, 2012) and Kerman. Papp, 1979 Material examined: 6♀, Kerman, Kuhpayeh, Deh Lolo, 30°30´03.…”
Section: Distribution In Iranmentioning
confidence: 99%
“…Tehran (Fischer 1990), Lorestan (Ghahari et al, 2012a, Opius (Phaedrotoma) exiguus), Sistan & Baluchestan (Khajeh et al, 2014) and Kerman. (Fischer, 1964) (Fig.…”
Section: Distribution In Iranmentioning
confidence: 99%